Urea plus nitrate pretreatment of rice and wheat straws enhances degradation and reduces methane production in in vitro ruminal culture - Xiumin Zhang; Min Wang; Rong Wang; Zhiyuan Ma; Donglei Long; Hongxiang Mao; Jiangnan Wen; Lukuyu, Ben A.; Beauchemin, K.A.; Zhiliang Tan (Wiley, 2018)
Urea pretreatment of straw damages fiber structure, while nitrate supplementation of ruminal diets inhibits enteric methane production. The study examined the combined effects of these treatments on ruminal substrate biodegradation and methane production using an in vitro incubation system. Rice and wheat straws were pretreated with urea (40 g kg−1 straw dry matter, DM) and urea + ammonium nitrate (34 + 6 g kg−1 dry matter (DM), respectively), and each straw (control, urea, urea+nitrate) was used in batch culture incubations in three replications (runs).Urea pretreatment increased (P < 0.05) neutral‐detergent solubles (NDS) content (+17%) and in vitro DM degradation of rice straw, in comparison with control. Urea+nitrate pretreatment of rice and wheat straws had higher (P < 0.05) NDS content, in vitro DM degradation and propionate molar proportion, and lower (P < 0.05) acetate:propionate ratio and lower methane production with a decline of methanogens, in comparison to control.Urea+nitrate pretreatment combines positive effects of urea pretreatment and nitrate supplementation, and can be a potential strategy to improve ruminal biodegradation, facilitate propionate production and reduce methane production from lignified straws. © 2018 Society of Chemical Industry